FACTORS CONTRIBUTING TO NON-ADHERENCE TO ANTI-DIABETIC MEDICATION AMONG DIABETIC PATIENTS ATTENDING NDEJJE HEALTH CENTRE IV, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Abdul Rahim Khalid; Hassan Kasujja (Student's Journal of Health Research, 2023)
Background: The prevalence of Non-adherence to anti-diabetic medication is on the rise across the world. The purpose of this study was to find out the factors contributing to non-adherence to anti-diabetic medication among patients attending Ndejje Health Centre IV, Wakiso district. Methodology: A cross-sectional research design was used on diabetic patients aged 18-88 years, selected using a simple random sampling method and questionnaires to collect data which was analyzed using Microsoft Excel, and the results were presented as tables, graphs, and pie charts. Results: The majority 99.1% had type 2 diabetes mellitus and 57.3% had the disease for less than five years 90.4% reported hypertension as the most experienced comorbidity. 87% reported diabetic neuropathy as the most common complication. The reasons for non-adherence were; drugs being expensive (25%), not understanding the prescriptions (17.5%), and unavailability of anti-diabetics (16%). Conclusion: In conclusion, even though the majority of the respondents were adherent to their anti-diabetic medication, 34.3% were non-adherent, and they mentioned drugs being expensive as the biggest reason for this. Recommendations: Therefore, the researcher recommends the Ministry of Health ensure that drugs are available at health facilities and prescribers should explain the use, effects, and why these drugs are essential to patients.